The Usefulness of Reported Segmental Information for Stock Valuation in China: An Analysts’ Perspective - Guo, Xiang (2013)
With further widening of globalisation and acceleration of mergers and acquisitions, companies’ operation is no longer restricted to one industry and geographic location. It becomes increasingly pervasive that companies diversify across businesses and regions. Major accounting standard setters, such as U.S. FASB and IASB have already implemented in-depth studies. However, China is still in its very early stages regarding the study of segment disclosures. The study provides an empirical examination on how stock analysts in mainland China perceive the decision usefulness of segment disclosures through their actual use for earnings forecast and stock valuation. Using a sample of 221 analyst reports covering 90 companies included in SSE Composite Index 50 and SZSE Component Index, this study reports 5 major findings. Firstly, analysts are concerned about the performance of companies’ divisions for stock valuation However; sum-of-parts (SOP) analysis is still not prevalent by analysts for earnings forecast, although 10.86% of them use segment forecasts. Operating revenues, gross profit margin, and net profits are the most preferred items of information by analysts for valuation. Secondly, although geographic segmentation is the most favoured by management, it is the least used type of segmentation by analysts. It is found that analysts focus on geographic segments only if it performs significantly or out of expectation. The result is consistent with those by (Boatsman, et al., 1993). Thirdly, analysts sometimes focus on significant segments rather than analysing all operating segments. Besides, analysts not only concern about what is happening today but also what might happen tomorrow. Evidence can be found that analysts even considers segments that contribute less than 10% of the company’s operating revenue but perform significantly with more than 20% year-on-year growth rate or those might contribute considerably in the future. They expect earnings growth based on companies’ investment plan and prosperity of each segments. Fourthly, only 55.4% of the sample companies disclosed segment information in segment reports while as high as 44.6% of the 74 firms reported segment information only in directors’ reports. Last but not the least, research analysts focus on different aspects of segmental information when covering companies in different industry.